2020
DOI: 10.1152/ajprenal.00295.2020
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the tubule: pathological variants of LRP2, encoding the megalin receptor, result in glomerular loss and early progressive chronic kidney disease

Abstract: Pathogenic variants in the LRP2 gene, encoding the multiligand receptor megalin, cause a rare autosomal recessive syndrome: Donnai-Barrow/Facio-Oculo-Acoustico-Renal (DB/FOAR). Due to the rarity of the syndrome, the long-term consequences of the tubulopathy on human renal health have been difficult to ascertain and the human clinical condition has hitherto been characterized as a benign tubular condition with asymptomatic low-molecular-weight proteinuria. We investigated renal function and morphology in a muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Additionally, we have reported megalin downregulation in kidney tissue from IgAN patients [16]. Inherited megalin deficiency is found to pose an increased risk of renal decline, which is in line with a genome-wide association study showing that single nucleotide polymorphisms in LRP2 are associated with low eGFR [17,18]. Together, these findings indicate that the proximal tubule megalin may be likely to serve as a biomarker for chronic kidney disease (CKD) progression in IgAN.…”
Section: Introductionsupporting
confidence: 80%
“…Additionally, we have reported megalin downregulation in kidney tissue from IgAN patients [16]. Inherited megalin deficiency is found to pose an increased risk of renal decline, which is in line with a genome-wide association study showing that single nucleotide polymorphisms in LRP2 are associated with low eGFR [17,18]. Together, these findings indicate that the proximal tubule megalin may be likely to serve as a biomarker for chronic kidney disease (CKD) progression in IgAN.…”
Section: Introductionsupporting
confidence: 80%
“…BMI1 [327], AMH (anti-Mullerian hormone) [328], E2F1 [329], PF4 [330], VASH2 [331], GRIN1 [332], CYP11B2 [333], COMP (cartilage oligomeric matrix protein) [334], DES (desmin) [335], ANGPTL3 [336], CYP3A5 [337], DPEP1 [338], LRP2 [339], AGXT2 [340], FABP1 [341], SLC22A12 [342], CUBN (cubilin) [343], MIOX (myo-inositol oxygenase) [344], ARG2 [345], KHK (ketohexokinase) [346], CYP2C8 [347], SLC2A9 [348], GC (GC vitamin D binding protein) [349], VNN1 [350], NOX4 [351], EPHX2 [352], AKR1C3 [353], NR4A3 [354], PFKFB2 [355], SLC22A6 [356], F11 [357], SLC22A2 [358], AQP2 [171], EGF (epidermal growth factor) [359], KNG1 [360], SERPINA5 [361], KL (klotho) [362], ACE2 [363], NPNT (nephronectin) [364], SLC47A1 [358], MGAM (maltase-glucoamylase) [365], AQP3 [366], AZGP1 [367], GALNT3 [368], DPP4 [369], STC1 [370], ABCB1 [371], ERRFI1 [372], TREH (trehalase) [373], MANBA (mannosidase beta) [374], ERBB4 [375], VCAM1 [376] and ALB (albumin) [377] might play an important role in the pathophysiology of AKI. BMI1 [378], IGF2 [379], PRKCB (protein kinase C beta) [380], CCL5 [381], E2F1 [382], PF4 [111], CYP11B2 [383], WNT3A [384], COMP (cartilage oligomeric matrix protein) [385], DES (desmin) [335], ANGPTL3 [386], CYP3A5 [387], LRP2 [388], PAH (phenylalanine hydroxylase) [389], HMGCS2 [390], AGXT2 [391], FABP1 [392], CUBN (cubilin) [393], DIO1 [394], MIO...…”
Section: Discussionmentioning
confidence: 99%
“…Musante et al [437], Han et al [438], Zhang et al [439], Sato et al [440], Yang et al [441], El-Aouni et al [442], Perisic et al [443], Chung et al [444], Wilkening et al [445], Kahvecioglu et al [446], Hu et al [447] and Worthmann et al [448] revealed that ALB (albumin), KLF15, ATF3, LPL (lipoprotein lipase), CUBN (cubilin), ILK (integrin linked kinase), PLEKHH2, TNF (tumor necrosis factor), CCR2, SPON2, LRRC55 and IGFBP1 might be the potential targets for FSGS diagnosis and treatment. Alves et al [449], Ma et al [450], Esposito et al [451], Ai et al [452], Lu et al [453], Bui et al [454], Bao et al [455], Zuo et al [456], Su et al [457], Wang et al [458], Šalamon et al [459], Harskamp et al [460], Ćwiklińska et al [461], Hishida et al [462], Gunay-Aygun et al [463], Simpson et al [464], Svenningsen et al [465], Wang et al [466], Rao et al [467], Chen et al [468], Bedin et al [469], Cao et al [470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474], Liu and Zhuang [475], Feng et al [476], Yu et al [477], Reed et al [478], Milillo et al [479], Chen et al [74], Chen et al [480], Vieira et al [76], Charlton et al [481], Shi et al [482], Zhou et al [483], Nazari et al [241], Greene et al [484], Lazar et al [485], Jobst-Schwan et al [486], Du et al [487], Liu et al [85], Liu et al [488], Liu et al [489], Lee et al [490], Wen et al [491], Sakai et al [492], Zhang et al [493], Wang et al [494], CD5L Castelblanco et al [251], Chen et al [495], Swanson et al [496], Ksiazek, [497], Li et al [498], Zhang et a...…”
Section: Discussionmentioning
confidence: 99%